Innovative Pickup Car Cooling System Based on Thermoelectric Coupled With Heat Pipe Sink: Innovative pickup car cooling system based on thermoelectric coupled with heat pipe sink - Ragil Sukarno; Muhammad Rafael; Nugroho Gama Yoga; Darwin Rio Budi Syaka; Agus Agung Permana; Yohanes Gunawan; Desy Kurniawati (Universitas Muhammadiyah Magelang, 2025)
Pickup cars are one of the most important means of transportation in the distribution of goods and logistics. However, many customers choose pickup cars without air conditioning because they are less expensive and more energy-efficient, resulting in lower operating costs. Car air conditioning systems generally utilize vapor compression systems, which consume a significant amount of energy. Additionally, some studies on thermoelectric cooling face challenges due to incompatible and difficult-to-install designs within vehicle cabins. To address this issue, this research was conducted on developing an innovative compact air conditioning (AC) system for the cabin of a pickup car. This system utilizes thermoelectric cooling (TEC) combined with a heat pipe sink. This cooling system features a practical and installation-friendly design compared to previous work, which can be integrated into existing pickup models without significant modifications. It is designed as a cooling box that generates and circulates cold air within the cabin. In this testing, the cooling box comprises six-unit thermoelectric cooling, where each unit varies using one-stage TEC modules and two-stage TEC modules. A 175-watt and 200-watt heat was applied and varied in the cabin to simulate the cooling load, and the air outlet duct's velocity also varied at 2 m/s and 3 m/s. The results showed that the thermoelectric cooling systems can significantly reduce cabin temperature increases, lowering the rise by 11.0 Â°C for a single-stage TEC system and by 10.8 Â°C for a double-stage TEC system compared to the cabin without a cooling system. The highest COP value of 1.4 was obtained in the single-stage TEC cooling system at a velocity of 3 m/s. The results show the potential of an innovative thermoelectric cooling (TEC) system when combined with heat pipes, offering an alternative cooling solution for the cabin of a pickup car. This proposed cooling system can be adapted for vehicles that require compact and energy-efficient cooling solutions.